EKSTRAKSI KOLAGEN IKAN MANYUNG DAN IKAN KAKAP SEBAGAI ALTERNATIF KOLAGEN - Anggari Linda Destiana; Stefani Harum Sari (BIO-SITE |Biologi dan Sains Terapan, 2018)
Total fish consumption during 2011-2015 showed an increase of 6.27%. The waste is estimated to be about 75% of the total weight of the fish. Thirty percent of the total 75% of fish processing waste is bone and skin. The collagen sources on the market is limited to cowhide and pig skin derived. Therefore, collagen from fish is expected to be an acceptable alternative source for all people because of its high availability and no risk of disease transmission. This study aimed to determine the difference of collagen content in manyung fish and snapper fish. Collagen extraction of manyung fish and snapper fish was done using alkaline and acidic solution. The soluble collagen concentration was measured by the standard Bradford solution using a UV-Vis spectrophotometer. The collagen concentration of manyung skin, snapper skin, manyung bone, snapper bone, and snapper scales obtained were 206.167; 202.833; 106.167; 77.833; and 24.50 ppm. The skin of manyung fish has the highest collagen content compared to other samples.